(untitled) (Boletin Médico de Postgrado, 2020)
With the objective of determining the ototoxic effects of cisplatin and its relationship with the onset of hearing loss in patients with cervical cancer who attended the Autonomous Oncology Service of Lara state, during the period October 2017-February 2018; A cross-sectional descriptive study was conducted, obtaining 16 patients, being the most affected the age group between 36-45 years (43.25%), and the ranges of 25-35 years and 46-55 years (25%, respectively) . Hearing symptoms before starting treatment were hearing loss (6.25%); After the first and second cycle, tinnitus was reported (62.5% and 68.75%), being most of the acute type (60% and 81.81%) and hearing loss (37.5% and 31%). 25%). The audiometric values at the beginning were superficial hypoacusis for 25db (31.25%) and 30db (25%); however, after the first and second cycle was hearing loss Surface-type neurosensory with a curve suggestive of grade I acoustic trauma with values of 35db (31.25%) and 40db (31.25%), respectively. The audiometric findings showed that 56.25% had superficial hearing loss at baseline; but, then, 50% were reported with superficial sensorineural hearing loss with a curve suggestive of grade I acoustic trauma, after both cycles. The results obtained allow the early identification of patients susceptible to developing hearing loss after adjuvant treatment with cisplatin.